Importance of phosphorus and potassium in soil-specific nutrient management for wet-season rice in Cambodia - Kong, Kea; Hin, Sarith; Seng, Vang; Ismail, Abdelbagi M.; Vergara, Georgina; Choi, Il-Ryong; Ehara, Hiroshi; Kato, Yoichiro (Experimental agriculture, 2020)
Rice is widely grown in rainfed lowlands during the wet season in the Mekong region. Limited nutrient availability is a common constraint on crop yield, and the optimal rate of fertilizer application depends on the soil type. The objective of our study was to evaluate rice productivity and the economic feasibility of various nutrient management regimes in Cambodia. We conducted field experiments on three soil types (Prey Khmer, Prateah Lang, and Toul Samroung, equivalent to Psamments, Plinthustalfs, and Endoaqualfs, respectively) in four provinces (Battambang, Kampong Thom, Pursat, and Siem Reap) during the 2016 and 2017 wet seasons to compare nine (2016) and seven (2017) N–P–K combinations. Grain yield ranged from 0.9 to 4.8 t ha −1 in 2016 and from 1.0 to 5.2 t ha −1 in 2017, depending on soil type and nutrient management. The Prey Khmer soil contained around 80% sand, and rice yield responded most weakly to nutrient management. The moderate fertilizer input in the current soil-specific recommendation was effective on this soil type. However, on more fertile soils with a higher clay content and a higher cation-exchange capacity (Toul Samroung and Prateah Lang), an additional 20 kg N ha −1 combined with adding 15 kg ha −1 of P 2 O 5 or 20 kg ha −1 of K 2 O significantly increased yield and economic return. Although P and K use during Cambodia’s wet season is uncommon, our results demonstrate the importance of these nutrients in improving the country’s rice production.